Alternative splicing of the Caenorhabditis elegans lev‐11 tropomyosin gene is regulated in a tissue‐specific manner. Issue 10 (15th November 2018) - Watabe, Eichi; Ono, Shoichiro; Kuroyanagi, Hidehito
Abstract: Tropomyosin isoforms contribute to generation of functionally divergent actin filaments. In the nematode Caenorhabditis elegans, multiple isoforms are produced from lev‐11, the single tropomyosin gene, by combination of two separate promoters and alternative pre‐mRNA splicing. In this study, we report that alternative splicing of lev‐11 is regulated in a tissue‐specific manner so that a particular tropomyosin isoform is expressed in each tissue. Reverse‐transcription polymerase chain reaction analysis of lev‐11 mRNAs confirms five previously reported isoforms (LEV‐11A, LEV‐11C, LEV‐11D, LEV‐11E and LEV‐11O) and identifies a new sixth isoform LEV‐11T. Using transgenic alternative‐splicing reporter minigenes, we find distinct patterns of preferential exon selections in the pharynx, body wall muscles, intestine and neurons. The body wall muscles preferentially process splicing to produce high‐molecular‐weight isoforms, LEV‐11A, LEV‐11D and LEV‐11O. The pharynx specifically processes splicing to express a low‐molecular‐weight isoform LEV‐11E, whereas the intestine and neurons process splicing to express another low‐molecular‐weight isoform LEV‐11C. The splicing pattern of LEV‐11T was not predominant in any of these tissues, suggesting that this is a minor isoform. Our results suggest that regulation of alternative splicing is an important mechanism to express proper tropomyosin isoforms in particular tissue and/or cell types in C. elegans .